Incomplete Information, Debt Issuance, and the Term Structure of Credit Spreads - Benzoni, Luca; Garlappi, Lorenzo; Goldstein, Robert (Management Science, 2023)
We derive a firm’s debt issuance policy when managers have an informational advantage over creditors and face debt restructuring costs. In our model, regardless of how poor their private signal is, managers of firms that can access the credit market avoid default by issuing new debt to service existing debt. Therefore, only bonds of firms that have exhausted their ability to borrow are subject to jump-to-default risk because of incomplete information and, in turn, command a jump-to-default risk premium. We document that our model captures many salient features of the corporate bond market. This paper was accepted by Kay Giesecke, finance. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4529 .